98.3k views
3 votes
Solve the given equation.



√(6x-1)+1=5

User Kulesa
by
5.0k points

2 Answers

5 votes
radical 6x-1 = 5-1
radical 6x-1=4
square both sides to get rid of radical
6x-1=16
6x= 16+1
6x=17
divide by 6, x=17/6
User Nrapopor
by
5.0k points
4 votes

Answer:

x =
(17)/(6)

Explanation:

Given


√(6x-1) + 1 = 5 ( subtract 1 from both sides )


√(6x-1) = 4 ( to clear the radical, square both sides )

6x - 1 = 4²

6x - 1 = 16 ( add 1 to both sides )

6x = 17 ( divide both sides by 6 )

x =
(17)/(6)

User Nazila
by
4.9k points